Palestinian pre-service mathematics teachers’ self-efficacy levels and performance in statistics - Abed, Saja (My University, 2014)
MATEMATİK ÖĞRETMEN ADAYLARININ İSTATİSTİK DERSİ KONULARINDAKİ KAVRAM YANILGILARI AND İSTATİSTİK DERSİNE YÖNELĠK ÖZ YETERLILIK INANÇLARI Bu çalışmanın amacı, matematik öğretmen adaylarının istatistik dersi konularındaki kavram yanılgılarının ve istatistik dersine yönelik

yeterlilik inançlarının incelenmesidir. Bu çalışmada nitel ve nicel veriler bir arada kullanılmıştır. Araştırmanın örneklemini 2013-2014 öğretim yılı, Filistin Cumhuriyeti'nin Al-Quds ve Al-Quds Open Üniversitesi Fen Fakültesi’nin toplam 100 Matematik öğretmen adayı oluşturmaktadır. Veri toplama araçları olarak İstatistik Kavram Testi ve İstatistik Dersine Yönelik Öz Yeterlilik İnanç Ölçeği kullanılacaktır. Veri analizinde frekans ve yüzde oranları, basit korelasyon kullanılmıştır. Anahtar Sözcükler: Istatistik Dersi, Matematik Öğretmen Adayları, Öz Yeterlilik Inancı, Kavram Yanılgıları. ABSTRACT PALESTINIAN PRE-SERVICE TEACHERS’ CONCEPTUAL KNOWLEDGE AND SELF-EFFICACY LEVELS IN STATISTICS Misconceptions in statistics and low self-efficacy are common problems for pre-service teachers which need more concern in order to improve the educational system. This study aimed to explore pre-service mathematics teachers’ mistakes in statistics and to measure their self-efficacy beliefs. The present study was conducted at the 2013 – 2014 academic year with a total number of 100 graduate pre-service mathematics teachers who were in their last academic year in the mathematics department of two Palestinian universities; Al-Quds University and Al-Quds Open University. Data was collected utilizing two questionnaires: the Statistics Self- Efficacy Belief Instrument and Statistics Concept Inventory. Descriptive statistics and correlation and were used in data analysis. Data analysis showed that participants’ statistics achievement was moderate. They had some common mistakes in probability, normal distribution, hypothesis testing, interpreting graphics, sampling distributions, and correlation. They had low to moderate level of self-efficacy beliefs in statistics. Key Words: Statistics Lesson, Pre-Service Mathematics Teachers, Misconception, Self Efficacy Belief.
Keywords: Eğitim; Matematik; Öğretmenler-- Ortaöğretim